An International Consortium Update: Pathophysiology, Diagnosis, and Treatment of Polycystic Ovarian Syndrome in Adolescence - Ibáñez, Lourdes; Oberfield, Sharon E; Witchel, Selma; Auchus, Richard J; Chang, R Jeffrey; Codner, Ethel; Dabadghao, Preeti; Darendeliler, Feyza; Elbarbary, Nancy Samir; Gambineri, Alessandra; Garcia Rudaz, Cecilia; Hoeger, Kathleen M; et al. (Hormone research in paediatrics, 2017)
This paper represents an international collaboration of paediatric endocrine and other societies (listed in the Appendix) under the International Consortium of Paediatric Endocrinology (ICPE) aiming to improve worldwide care of adolescent girls with polycystic ovary syndrome (PCOS)1. The manuscript examines pathophysiology and guidelines for the diagnosis and management of PCOS during adolescence. The complex pathophysiology of PCOS involves the interaction of genetic and epigenetic changes, primary ovarian abnormalities, neuroendocrine alterations, and endocrine and metabolic modifiers such as anti-Müllerian hormone, hyperinsulinemia, insulin resistance, adiposity, and adiponectin levels. Appropriate diagnosis of adolescent PCOS should include adequate and careful evaluation of symptoms, such as hirsutism, severe acne, and menstrual irregularities 2 years beyond menarche, and elevated androgen levels. Polycystic ovarian morphology on ultrasound without hyperandrogenism or menstrual irregularities should not be used to diagnose adolescent PCOS. Hyperinsulinemia, insulin resistance, and obesity may be present in adolescents with PCOS, but are not considered to be diagnostic criteria. Treatment of adolescent PCOS should include lifestyle intervention, local therapies, and medications. Insulin sensitizers like metformin and oral contraceptive pills provide short-term benefits on PCOS symptoms. There are limited data on anti-androgens and combined therapies showing additive/synergistic actions for adolescents. Reproductive aspects and transition should be taken into account when managing adolescents.